An Adaptive Multimedia Messaging Service Framework for Mobile Telemedicine System - Setyono, Andik (International Journal of Interactive Mobile Technologies (iJIM), 2015)
This paper presents an adaptive MMS framework to build a mobile telemedicine system for sending multimedia messages and also for streaming audio and video files. With the proposed framework, the capability of MMS can be increased to send and receive multimedia files of larger sizes without degrading the quality of data which is not possible with the present MMS system. This feature is particularly important for telemedicine environment as good quality of multimedia data is required to accomplish accurate medical diagnosis. The experimental results demonstrate that the proposed framework outperforms the existing MMS system with regard to the file size that can be transmitted and also with regard to the quality of data. The modified MMS framework is adaptive in the sense that it allows transmission of different sizes and types of multimedia messages. This framework can form the basis for developing a practical mobile telemedicine system.